Construction of a Chimeric Secretory IgA and Its Neutralization Activity against Avian Influenza Virus H5N1. (13th February 2014) - Li, Cun; An, Xiaoping; Butt, Azeem Mehmood; Zhang, Baozhong; Zhang, Zhiyi; Wang, Xiaona; Huang, Yong; Zhang, Wenhui; Zhang, Bo; Mi, Zhiqiang; Tong, Yigang
Abstract : Secretory immunoglobulin A (SIgA) acts as the first line of defense against respiratory pathogens. In this assay, the variable regions of heavy chain (VH) and Light chain (VL) genes from a mouse monoclonal antibody against H5N1 were cloned and fused with human IgA constant regions. The full-length chimeric light and heavy chains were inserted into a eukaryotic expressing vector and then transfected into CHO/dhfr-cells. The chimeric monomeric IgA antibody expression was confirmed by using ELISA, SDS-PAGE, and Western blot. In order to obtain a dimeric secretory IgA, another two expressing plasmids, namely, pcDNA4/His A-IgJ and pcDNA4/His A-SC, were cotransfected into the CHO/dhfr-cells. The expression of dimeric SIgA was confirmed by using ELISA assay and native gel electrophoresis. In microneutralization assay on 96-well immunoplate, the chimeric SIgA showed neutralization activity against H5N1 virus on MDCK cells and the titer was determined to be 1 : 64. On preadministrating intranasally, the chimeric SIgA could prevent mice from lethal attack by using A/Vietnam/1194/04 H5N1 with a survival rate of 80%. So we concluded that the constructed recombinant chimeric SIgA has a neutralization capability targeting avian influenza virus H5N1 infection in vitro and in vivo.